Porous and nonporous orbital implants for treating the anophthalmic socket: A meta-analysis of case series studies - Schellini, Silvana [UNESP]; Jorge, Eliane [UNESP]; Sousa, Roberta [UNESP]; Burroughs, John; El-Dib, Regina (Taylor & Francis, 2016)
Purpose: To assess the efficacy and safety of porous and nonporous implants for management of the anophthalmic socket.Methods: Case series meta-analysis was conducted with no language restriction, including studies from: PUBMED, EMBASE and LILACS. Study eligibility criteria were case series design with more than 20 cases reported, use of porous and/or nonporous orbital implants, anophthalmic socket and, treatment success defined as no implant exposure or extrusion. Complications rates from each included study were quantified. Proportional meta-analysis was performed on both outcomes with a random-effects model and the 95% confidential intervals were calculated. Results: A total of 35 case series studies with a total of 3,805 patients were included in the meta-analysis. There are no studies comparing porous and nonporous implants in the anophthalmic socket treatment. There was no statistically significant difference between porous polyethylene (PP) and hydroxyapatite (HA) on implant exposure: 0.026 (0.012-0.045) vs 0.054 (0.041-0.070), respectively and, neither on implant extrusion: 0.0042 (0.0008-0.010) vs. 0.018 (0.004-0.042), respectively. However, there was a significant difference supporting the use of PP when compared to bioceramic implant: 0.026 (0.012-0.045) vs. 0.12 (0.06-0.20), respectively, on implant exposure. Conclusion: PP implants showed lower chance of exposure than bioceramic implant for anophthalmic socket reconstruction, although we cannot rule out the possibility of heterogeneity bias due to the nature and level of evidence of the included studies. Clinical trials are necessary to expand the knowledge of porous and nonporous orbital implants in the anophthalmic socket management.
Keywords: Anophthalmic socket; Case series study; Meta-analysis; Nonporous implant; Porous implant